Sibutramine as a Cause of Sudden Cardiac Death - Miguel Rodriguez-Guerra; Mayank Yadav; Manoj Bhandari; Archna Sinha; Jonathan N. Bella; Eduard Sklyar (Case Reports in Cardiology)
Importance. Sibutramine was withdrawn from the US market due to association with adverse cardiovascular outcomes especially with patients having preexisting cardiac disease. However, continued presence of sibutramine in herbal medications is a concern to public safety. Results. We report a case of a patient with no evidence of previous coronary heart disease, who presented with non-ST elevation acute coronary syndrome (NSTE-ACS). Urgent coronary catheterization showed nonobstructive coronaries. However, patient died unexpectedly within 24 hours of admission. The patient denied toxic habits but was taking over-the-counter weight loss herbal supplements. Complete autopsy was performed which showed sibutramine in the toxicology. Patient died due to complications of acute inadvertent intoxication of sibutramine. Conclusion and Relevance. This is the first case report in literature showing association of sibutramine to sudden cardiac death in patients with no prior cardiac history. The continued presence of sibutramine in some over-the-counter weight loss formulations is a very concerning public health issue.